Response to Michael Kaler - Bivins, Jason (Bulletin for the study of religion, 2016)
This response focuses primarily on Kaler's engagement with: the analytical problem of interpreting music without texts, the status of religious "experience" as a disciplinary category, and the relationship between "mainstream" and "avant-garde" musics.